Expériences de discrimination chez les Noirs et les Autochtones au Canada, 2019 - Gouvernement du Canada, Statistique Canada (2022)
À l'aide des données de l'ESG de 2019 sur la sécurité des Canadiens (victimisation), le présent article de Juristat examine les expériences de discrimination dans la vie quotidienne des Canadiens, avec un accent particulier sur les expériences des populations noires et des Premières Nations, des Métis et des Inuits vivant au Canada.
Last Modified: 2022-02-16
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; discriminations; histoire et politique; inégalités; justice sociale; pol5480; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; violences

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis